ENHANCING ENGLISH FLUENCY USING THE READING ALOUD FITUR IN ALFA PTE APPLICATION - fachriyah, eva - (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2024)
This study investigates the impact of implementing the reading aloud feature in the ALFA PTE application on increasingg English fluency in reading skill among intermediate-level students at an urban language school. The research method used is mix method, which is survey design. Data were collected through observations, questionnaire, and pre-test and post-test. This study used a survey design on first-semester students in the communication science program. The score of reading fluency of pre-test and post-test were analyzed using the T-test. The research finding based on survey responses highlighted positive perceptions of the application's usability, its effectiveness in enhancing pronunciation skills, and its motivational benefits. These findings underscore the application's role in advancing English reading proficiency and stimulating student engagement. Based on the quantitative result using T-test analysis, it could be said that video project could increase reading fluency for student. Future research could further investigate the long-term effects and optimize educational technology applications to meet diverse learning needs effectively